Green urine: A rare benign side effect of propofol - Rawal, Gautam; Garg, Nitin; Rasool Wani, Umar; Yadav, Sankalp (International Journal of Medical Research and Review, 2015)
Discoloration of urine is a well known occurrence in an intensive care setting, and is always a cause of concern to look out for the reason of the color, so as to differentiate between benign and pathological causes. The authors present a case of 52 year male who was noticed to be passing green colored urine probably secondary to intravenous propofol administration for induction of general anesthesia. The green color of urine due to propofol is believed to be as a result of the green phenolic metabolite of propofol produced in the liver and excreted through urine. Though this discoloration of urine is benign, non-nephrotoxic and gets reversed after discontinuation of the drug, it still raises alarm in the mind of the treating physician. This case demonstrates a rare, but benign side effect of propofol.